KADAR ASAM URAT SERUM DAN KOMPONEN SINDROM METABOLIK - MI Diah P; Banundari Rachmawati; Purwanto AP (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
The incidence of metabolic syndrome (MetS) is significantly increasing. The elevated serum uric acid (SUA) level is correlated with the metabolic risk of cardiovascular. The relationship between SUA levels and components of MetS has been inconsistent. The aim of this study was to know the correlation between SUA level and component of MetS by analyzng. This study was a cross-sectional design conducted on healthy people at the Medical Check Up (MCU) Clinic, Dr. Moewardi Hospital, Surakarta from June 2012 until February 2013. MetS was defined according to the 2005 International Diabetes Federation (IDF) criteria. The statistical analysis was done by Student’s T test, Pearson or Spearman correlation coefficients. The researchers considered p<0.05 as statistically significant with a 95% confidence interval. A total of 80 healthy subjects, (range 19–57 years) were enrolled into this study. MetS was diagnosed in 40 persons where men (62.5%) were more than women and the non-MetS in women (62.5%) were more than men. In this study, a positive correlation was found between SUA and systolic blood pressure, diastolic blood pressure and waist circumference (Pearson r=0.354, 0.495, 0.399, respectively, p<0.05) in women, but not in men. The SUA was positively correlated with systolic blood pressure, diastolic blood pressure and waist circumference, particularly in women. A long term study is needed to investigate the consequence of increasing the SUA level in metabolic disorders and hormonal influences as well.